On groups factorized by two subgroups with Chernikov commutants - Chernikov, N. S. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We establish results concerning the almost solvability and other properties of groups factorized by two subgroups with finite or Chernikov commutants.